2021
DOI: 10.1002/ajoc.202100154
|View full text |Cite
|
Sign up to set email alerts
|

Two‐step Conformational Control of a Dibenzo Diazacyclooctane Derivative by Stepwise Protonation

Abstract: The conformational control of a dibenzo-1,5diazacyclooctane (DACO) derivative with tertiary and secondary amino groups by stepwise protonation is investigated by single crystal X-ray diffraction analysis, computational simulation, and variable temperature NMR measurements. The DACO derivative undergoes two-step protonation, to afford bent-shape monoprotonated and diprotonated species, whose conformations are different from each other. The monoprotonated form is characterized by a Tröger'sbase-like proton-bridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…More recently, Ishiwari and co-workers showed that 1,5-diaza analogues adopt straight-shape twisted conformation with a transannular NH HB, but change to more or less bent boat-type structures upon mono-or di-protonation. [12] The involvement of a putative intramolecular HB was also reported between Se and H of the methylene groups in the selenated analog of 1, namely dibenzo-1,5-selenocine 2-Se [13] (Figure 1). In this work, the authors noticed shorter distances in (calculated) 2-SeB than in 2-SeC, which "may indicate a stronger CÀ H…Se nonbonded interaction in 2-SeB than in 2-SeC".…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…More recently, Ishiwari and co-workers showed that 1,5-diaza analogues adopt straight-shape twisted conformation with a transannular NH HB, but change to more or less bent boat-type structures upon mono-or di-protonation. [12] The involvement of a putative intramolecular HB was also reported between Se and H of the methylene groups in the selenated analog of 1, namely dibenzo-1,5-selenocine 2-Se [13] (Figure 1). In this work, the authors noticed shorter distances in (calculated) 2-SeB than in 2-SeC, which "may indicate a stronger CÀ H…Se nonbonded interaction in 2-SeB than in 2-SeC".…”
Section: Introductionmentioning
confidence: 77%
“…Interestingly, the B/C interchange temperature could be raised from −60 to 60 °C by finely tuning the position and NCI properties of the substituents. More recently, Ishiwari and co‐workers showed that 1,5‐diaza analogues adopt straight‐shape twisted conformation with a transannular NH HB, but change to more or less bent boat‐type structures upon mono‐ or di‐protonation [12] …”
Section: Introductionmentioning
confidence: 99%
“…More recently, Ishiwari and coworkers showed that 1,5-diaza analogues adopt straight-shape twisted conformation with a transannular NH HB, but change to more or less bent boat-type structures upon mono-or diprotonation. [12] The involvement of a putative intramolecular HB was also reported between Se and H of the methylene groups in the selenated analog of 1, namely dibenzo-1,5-selenocine 2-Se [13] (Figure 1). In this work, the authors noticed shorter distances in (calculated) 2-SeB than in 2-SeC, which "may indicate a stronger C-H---Se nonbonded interaction in 2-SeB than in 2-SeC".…”
Section: Introductionmentioning
confidence: 77%